Civil Democracy Protection : Success Conditions of Non-Governmental Organisations in Comparison - Backes, Uwe 1960- HerausgeberIn; Lindenberger, Thomas 1955- HerausgeberIn (Routledge Studies in Extremism and Democracy, 2024)
Civil Democracy Protection is an overview of attempts by organisations to oppose groups that are perceived to threaten democracy. The book traces the history of civil democracy protection actors from the establishment of democratic constitutional states up to the present day and develops a set of systematic and comparative approaches. The central question it explores is: What significance do civil actors have for the establishment and consolidation of democratic constitutional states, especially in relation to the protection of democracy by state institutions? The volume includes contributions from historians and social scientists, who combine idiographic approaches that focus on the specifics of individual cases with nomothetic approaches that aim to provide generalisable insights, incorporating historical experiences from various European countries and the USA in the 20th and early 21st century. This book will be of interest to scholars of democracy protection, civil society, consolidation of democracy, and anti- extremism. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 International license